(untitled) (Anclajes, 2024)
Part of the poetry of Abigael Bohórquez (1936-1995) can be read as poetry of homosexual testimony. Specifically, his last collection of poems, his poetic testament, Poesida (1996), allows for this reading, since this cruel but supportive document seeks to put shame on the side of the heteronormative discourse, the one that reacted by condemning homosexual practices at the height of the Hiv/Aids pandemic in the 1980s & 1990s of the 20th century. Poesida will be studied from the poetics of misrepresentation, as a proposal for analysis for the dissident resistance to the discursive normalization that the collection of poems offers, both in the confrontation of the literary tradition, as well as in the poetic space and in the autobiographical references. Bohórquez builds a mural, a testimony, a series of songs and portraits so as not to forget, dignify and resist the shame with which they tried to classify those who died with the weight of stigma and guilt.